(untitled) (Global Conference on Medical and Health Sciences, 2026)
Transport-logistics infrastructure holds strategic importance for a country’s economic stability and the efficient execution of trade flows. A sustainable transport-logistics system enhances the national economy’s competitiveness by ensuring financial stability, attracting investments, and improving project efficiency. International experience demonstrates that financial strategies and investment project evaluation mechanisms are widely used to create sustainable transport-logistics infrastructure. For instance, in European countries, railway projects are implemented through public-private partnerships (PPPs), investment bonds, and project financing, resulting in high efficiency and profitability of transport services. In China, railway transport projects utilize “green bonds” and digital monitoring systems, which minimize investment risks.